Midwifery Care On by. R Age 16 Days With Spit on Pratama Clinic Arrabih Pekanbaru 2019: Midwifery Care On by. R Age 16 Days With Spit on Pratama Clinic Arrabih Pekanbaru 2019 - Widya Sari Intan (Journal of Midwifery and Nursing, 2020)
-Spit up is the return of milk that has been swallowed when or some time after drinking milk without contraction of the stomach wall. Spit up is a normal condition and is usually experienced by infants aged 0-6 months. The cause of the spit up is when the baby's breastfeeding technique is incorrect or after breastfeeding is not buried. The purpose of this care is to reduce the frequency of spit up in infants. The method used to reduce the frequency of spit up in infants is to improve breastfeeding techniques and burp the baby after breastfeeding. After Midwifery care for infants aged 0-6 months for four visits, the results Obtained are the frequency of spit-up experienced by babies aged 16 days has been reduced at the last visit. The conclusion with giving care about how to burp the baby and breastfeeding techniques that are good and right can be to reduce the frequency of spit up in infants. It is recommended to Midwifery care providers to be Able to hold counseling techniques on how to breastfeed properly and burp the baby after breastfeeding, so mothers who have babies aged 0-6 months are more calm in responding to the baby when experiencing spit up and pay more attention to good breastfeeding techniques and correct and burping the baby after breastfeeding.